Nanoparticles in dental biomaterials and their antimicrobial effect. A literature review - Illescas , Elian (2025)
The objective of this literature review is to compile evidence on the aggregation of nanoparticles in dental biomaterials and their antimicrobial effect. A systematic search was conducted across academic databases, including SciELO, PubMed, and Google Scholar, applying search filters to select 25 scientific articles published within the last eight years. Inclusion criteria prioritized studies published in Spanish or English since 2016, while excluding non-scientific sources and undated publications. Nanoparticles, particularly silver-based variants, enhance the antimicrobial properties of dental biomaterials, demonstrating efficacy against cariogenic pathogens such as Streptococcus mutans. Their use in dental treatments may mitigate infection risks. Nanoparticles represent a promising approach for developing more resistant and biocompatible biomaterials. Their antimicrobial action could aid in preventing infections in dental procedures. However, further research is required to better understand the mechanisms of action of nanoparticles in the oral environment and their safety in long-term clinical applications.